Traditional Andean contribution to the solution of irrigation problems: The specific case of the Altiplano - Dietschy, Beat R. (1984)
Peru is currently one of the most important countries in German development policy and technical cooperation. This fact, however, should not deceive us since it was the scene of a series of highly developed civilizations.